Costs and Compensation for the Innocent Accused - Mackinnon, Peter (The Canadian Bar Review, 1988)
This article examines the possibility that innocent accused might be compensated for the expense of defending themselves through cost awards or other payments. It reviews traditional and contemporary approaches, and challenges current Canadian thought on the subject on the basis that it does not address adequately the problem, and that it compromises unacceptably the presumption of innocence. Finally the article considers three leading cases which support the argument.